Analysis of ovarian reserve markers (AMH, FSH, AFC) in different age strata in IVF/ICSI patients - Ensieh Shahrokh Tehraninezhad; Fatemeh Mehrabi; Raheleh Taati; Vahid Kalantar; Elham Aziminekoo; Azam Tarafdari (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: The predictive roles of follicle stimulating hormone (FSH), anti-mullerian hormone (AMH) and antral follicle count (AFC) as ovarian reserve markers in women with different age groups are not established well. Objective: This study compares the value of FSH, AMH and AFC at the time of in vitro fertilization (IVF) treatment in different age groups. Materials and Methods: In this cross-sectional study, 103 women aged 20-43 years candidates for IVF/ICSI cycle were recruited. FSH, AMH and AFC on day 3 of menstrual cycle were measured. The relationship of these measured markers with outcome variables (oocytes number, number of frozen/fresh embryo and chemical and clinical pregnancy) was assessed in different age groups (i.e. 20-32, 33-37 and 38-43 years). Results: our results show that age was correlated with clinical pregnancy, oocyte count and fresh and frozen embryo (p<0.001). AMH, AFC and FSH were not correlated with clinical or chemical pregnancy at total population or age subgroups except the significant correlation of AFC with clinical pregnancy at 33-37 years old group. AFC was correlated with oocyte count and the number of fresh and frozen embryos in the ages group 20-32 years. In this age group, AMH was correlated with fresh and frozen embryos. AMH, AFC and FSH were correlated with oocyte count and the number of fresh embryos in age group 33-37 years. AMH was correlated with oocyte count and the number of fresh embryos in 38-43 years old group. Conclusion: We concluded that the age is the superior predictor of IVF outcome and AMH and AFC are variable predicting markers of ovarian reserve in different age groups.